ACE-ARBS-induced cholestasis: a case report - Oraijah, Abrar A.; Alghamdi, Mansour H.; Elnaggar, Ahmed M.; Ahmed, Amal A. (International Journal of Research in Medical Sciences, 2025)
Angiotensin-converting enzyme inhibitors (ACEIs) and angiotensin II receptor blockers (ARBs) are commonly utilized antihypertensive medications with a proven safety record. Nevertheless, they have been associated with few instances of drug-induced liver injury (DILI), namely cholestatic liver injury. This report details a case of recurrent cholestatic hepatotoxicity linked to both an ACE inhibitor and an angiotensin receptor blocker, emphasizing the diagnostic difficulties and potential for cross-reactivity. A 50-year-old female with hypertension developed progressive jaundice and pruritus two weeks after initiating an ACE inhibitor. Laboratory tests revealed a cholestatic pattern of liver injury, and extensive workup ruled out alternative etiologies. A liver biopsy confirmed drug-induced cholestasis. Following ACEI discontinuation, her liver function improved; however, two months later, she experienced recurrent cholestatic liver injury after switching to an ARB. The ARB was discontinued, and medical management with ursodeoxycholic acid, prednisolone, and N-acetylcysteine was initiated. The patient showed gradual biochemical improvement over follow-up, though prolonged cholestasis was noted. The recurrence of liver injury with the ARB suggests potential cross-reactivity between ACEIs and ARBs in susceptible individuals. ACEI- and ARB-induced cholestasis is a rare but significant adverse effect requiring early recognition and drug discontinuation. This case underscores the importance of considering drug-induced hepatotoxicity in patients with unexplained liver dysfunction and highlights the risk of recurrent injury with ARB substitution.